The patterning of the discursive space in search for the #goodlife: A network analysis of the co-occurrence of Instagram hashtags. Issue 1 (1st January 2023) - Loukianov, Anastasia; Burningham, Kate; Jackson, Tim
Abstract: Stories about what living well means are critical both to the maintenance of existing ways of living and to the possibility of envisioning and transitioning toward fairer and more sustainable futures. The implications of the stories told on social media for the possibility of such futures have yet to be explored. In this article we explore how the use of hashtags on Instagram shapes the visibility and recognizability of understandings of the good life in the discursive field created by #goodlife on the platform. Using network analysis, we map the co-occurrence of hashtags in 793 posts tagged #goodlife to explore the formation of hashtag-based narrative and hyperlink patterns. The visibility and recognizability of narrative patterns within this discursive space are shaped by interactional conventions and by algorithmic infrastructure, favoring corporate interests over sustainable and fair livelihoods. However, we also identify themes that could support fairer and more sustainable understandings of living well and reassert their ongoing importance.